A case of postpartum chronic subdural hematoma - Suyasha Rajbhandari; Pritam Gurung; Gopi Nepal; Samir Acharya; Basant Pant (Clinical Case Reports, 2021)
Abstract Headache is a common presentation during postpartum period. Anesthesiologist, obstetrician, and neurosurgeon should be aware of the possibility of subdural hematoma in patient complaining of headache following spinal anesthesia.